2005
DOI: 10.1039/b510340a
|View full text |Cite
|
Sign up to set email alerts
|

The benzil–benzilic acid rearrangement in high-temperature water

Abstract: The rearrangement of benzil is base (and not acid) catalyzed under conventional conditions (water-dioxane mixture around 100 uC). We examined this reaction in high-temperature water (HTW) between 300-380 uC with the intent of studying a reaction that proceeds solely by base catalysis in this more environmentally benign medium. The rearrangement proceeds in neutral HTW without addition of base, but the yield of rearrangement products is nearly insensitive to pH at near-neutral conditions. Adding larger amounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Py Cn • has been established as a catalyst for the oxidative cleavage of benzil to benzoic acid in methanol in air. Oxidative cleavage of benzil to benzoic acid is not common, generally in the presence of base benzil undergoes rearrangement to benzilic acid . However, the reaction of benzil (2.0 mmol) with Py Cn • (0.07 mmol) in methanol in the presence of triethylamine (0.03 mmol) and air at RT for 48 h affords benzoic acid (3.44 mmol), corresponding to 86% conversion (see experimental section in SI).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Py Cn • has been established as a catalyst for the oxidative cleavage of benzil to benzoic acid in methanol in air. Oxidative cleavage of benzil to benzoic acid is not common, generally in the presence of base benzil undergoes rearrangement to benzilic acid . However, the reaction of benzil (2.0 mmol) with Py Cn • (0.07 mmol) in methanol in the presence of triethylamine (0.03 mmol) and air at RT for 48 h affords benzoic acid (3.44 mmol), corresponding to 86% conversion (see experimental section in SI).…”
Section: Resultsmentioning
confidence: 99%
“…The preliminary investigation establishes that Py Cn • acts as a catalyst for the oxidative cleavage of benzil to benzoic acid in methanol in the presence of air. Oxidative cleavage of benzil to benzoic acid is not common, generally in the presence of base benzil undergoes rearrangement to benzilic acid . Thus, modeling of a catalyst for this redox reaction is significant in metallo-organic chemistry, and in this regard, the activity of Py Cn • is worthy.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these preliminary results and previous studies, , the catalytic cycle of this transformation was hypothesized as shown in Scheme . Ring opening of 2,3-diphenyloxirane 1a with aniline gives intermediate A .…”
mentioning
confidence: 89%
“…Among the most widely researched types of reactions are base-catalyzed reactions. Many types of reactions, such as aldol condensation, the Cannizzaro reaction, Michael addition, benzylic acid rearrangement, and hydrolysis, have been investigated. Recently, the control of base-catalyzed reactions in sub- and supercritical water using solid catalysts has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%